Marketing mix strategy through SWOT analysis method at PT. Toyo Maitsu Surabaya - Anisa Larasati; Rusdi Hidayat Nugroho (Enrichment : Journal of Management, 2023)
The company must act effectively and efficiently so that the business is able to survive and compete in any condition. In this case, the company needs to plan carefully, all long-term plans must focus on the survival of the company. A good and correct strategy is also required to ensure continuity and can help the company achieve its goals. The purpose of this study was to determine and analyze the marketing mix strategy using the SWOT analysis method in increasing sales volume implemented by PT Toyo Maitsu Surabaya. This study uses a descriptive qualitative research method. Data collection techniques in this study were carried out by means of in-depth interviews, distribution of questionnaires, and observation. The informants in this study were the owners, employees and consumers of PT Toyo Maitsu Surabaya. The data that has been collected, then analyzed using descriptive analysis methods and SWOT analysis. The results showed that PT Toyo Maitsu used the 7P marketing mix consisting of product, price, promotion, place, process, people and physical evidence. Based on the calculation results of the IFAS matrix table and EFAS matrix table, it is known that the IFAS value is 2.79 and the EFAS result value is 2.77, with the results of the analysis showing that PT Toyo Maitsu is in quadrant 1. It can be concluded that the main strategy of PT Toyo Maitsu is a strategy that supports policy aggressive growth (growth oriented strategy).